Appropriate Needle Length for Emergent Pediatric Needle Thoracostomy Utilizing Computed Tomography. (3rd September 2019) - Mandt, Maria J.; Hayes, Kari; Severyn, Fred; Adelgais, Kathleen
Abstract: Objective: Needle thoracostomy is a life-saving procedure. Advanced Trauma Life Support guidelines recommend insertion of a 5 cm, 14-gauge needle for pneumothorax decompression. High-risk complications can arise if utilizing an inappropriate needle size. No study exist evaluating appropriate needle length in pediatric patients. Utilizing computed tomography (CT), we determined the needle length required to access the pleural cavity in children matched to Broselow™ Pediatric Emergency Tape color.Methods: Three investigators reviewed chest CTs of children <13 years of age obtained between 2010 and 2015. Patient exclusions included those with a chest wall mass, muscle disease, pectus deformity, anasarca, prior open thoracotomy, inadequate imaging, or missing height documentation. We established 4 groups based upon Broselow™ color as determined by recorded height. Investigators, trained by a pediatric board-certified radiologist, obtained standardized CT measurements of chest wall thickness at 4 points: right/left second intercostal space at the midclavicular line (ICS-MCL) and right/left fourth intercostal space in the anterior axillary line (ICS-AAL). Our outcome was the median chest wall thickness and 95% confidence intervals for each Broselow grouping and anatomic site.Results: A total of 273 chest CTs were reviewed, of which 23 were excluded, for a resultant study population of 250 scans and 498 total measurements. Median patient age was 4 years, 52.8% were male. Children measuring Broselow Gray/Pink (<68 cm), had a median chest wall thickness at the 2nd ICS-MCL of 1.57 cm (95% CI 1.42 cm, 1.72 cm), 4th ICS-AAL 1.67 cm (95% CI 1.48 cm, 1.86 cm). Broselow Red/Purple (68.1–90 cm): 2nd ICS-MCL of 1.96 cm (95% CI 1.84 cm, 2.08 cm), 4th ICS-AAL 1.73 cm (95% CI 1.62 cm, 1.84 cm). Broselow Yellow/White (90.1–115cm): 2nd ICS-MCL of 2.12 cm (95% CI 2.03 cm, 1.22 cm), 4th ICS-AAL 1.91 cm (95% CI 1.8 cm, 2.01 cm). Broselow Blue/Orange/Green (>115.1 cm): 2nd ICS-MCL of 2.45 cm (95% CI 2.3 cm, 2.6 cm), 4th ICS-AAL 2.19cm (95% CI 2.02 cm, 2.36 cm).Conclusion: Median chest wall thickness varies little by height or location in children <13 years of age. The standard 5-cm needle is twice the chest wall thickness of most children. Commercially available 14 g or 16 g standard-length 3.8 cm (1½ inch) needles are of adequate length to access the pleural cavity, regardless of height as measured by Broselow LBT.